Surgical management and postoperative functional recovery of distal ulna tumors: a case report and literature review - Han, Yue-hua; Liang, Tian-jun; Zhu, Chen-xu; Kang, Sheng-jie; Wang, Dong-lai (Frontiers in Oncology, 2026)
IntroductionBone is the second most common site of metastasis for renal malignancies after the lung, with approximately 30% of metastatic renal cell carcinomas involving bone. Current research indicates that the common sites of bone metastasis from renal malignancies are mainly the axial skeleton. About 71% of patients with bone metastasis have multiple bone metastases. Cases of distal ulna metastasis of renal malignancies are rarely reported. At present, there are no standardized guidelines for the surgical treatment of distal ulna metastasis of renal malignancies. We report a case of distal ulna metastasis from renal malignancy. Additionally, we review the surgical techniques of distal ulna resection and their impact on wrist function over the past 20 years.Case PresentationA 61-year-old male patient came to the hospital due to pain and swelling in the left forearm for one month. The patient had undergone surgery for clear cell renal cell carcinoma of the left kidney, and biopsy confirmed metastatic clear cell renal cell carcinoma. He required surgical resection. In this case, the patient underwent wide segmental resection of a 10 cm tumor in the distal ulna without soft tissue reconstruction. Eleven months after surgery, the patient was able to achieve complete wrist joint mobility following active rehabilitation. The patient was discharged without complications and is now undergoing regular follow-ups every three months, as well as receiving monthly doses of the bone protective agent denosumab for the treatment of bone metastasis.ConclusionIn this case, the distal ulna tumor segment was extensively resected without reconstruction or prosthetic implantation. The patient had good wrist joint function in the short term. Different surgical methods for distal ulna resection impact the recovery of wrist joint function in patients. However, as all the literature reviews involved short- to medium-term follow-ups, longer-term follow-up may be needed to observe the recovery of wrist joint function at different time points in patients.